The interventions of the Italian Recovery and Resilience Plan: Energy efficiency in urban areas - Sgambati, Sabrina (TeMA - Journal of Land Use, Mobility and Environment, 2022)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of a continuous updating of emerging topics concerning relationships among urban planning, mobility and environment, through a collection of short scientific papers. The Review Notes are made of five parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. This section of the Review Notes explores a specific topic, related to cities, within the framework of the European program NextGenerationEU. This contribution deepens the topic of energy efficiency in urban areas, providing an overview of the proposed interventions to improve energy management and save natural resources in the Italian Recovery and Resilience Plan (NRRP). The aim is deepening how these measures are intended to make Italian cities more sustainable, livable and environmental-friendly. Furthermore, it highlights the main strategies, reforms, and interventions which have been activated in Italian cities, thanks to the NRRP investments.